The Influence Analysis Of Electronic Word Of Mouth On Purchase Intention Mediated By Brand Image On Lazada In Bandung City - Nurlianti, Fitri; Millanyani, Heppy (eProceedings of Management, 2023)
The development of technology every year has increased very rapidly, in this increasingly modern era, mostpeople in choosing or buying a product are influenced by technological sophistication. Over time, the businessworld is an example of this technological development, the emergence of online commerce or e-commerce.Lazada is an online store that is less popular than Shopee which are the most popular e-commerce platforms inIndonesia. Due to the large number of declines in Lazada, the problem to be discussed is Electronic Word ofMouth which affects Purchase Intention mediated by Brand Image. This study using quantitative approach withdescriptive analysis. The population are Lazada consumers in the city of Bandung. The sampling technique usedis non-probability sampling with a total 400 respondents and data collection in this study was carried out bydistributing online questionnaires via Google form, using a Likert scale. Data analysis used Structural EquationModel Partial Least Square (SEM-PLS) with SmartPLS 3.0 software. Based on the results of the study, theElectronic Word of Mouth variable influences Purchases Intention. Electronic Word of Mouth influences BrandImage. So it can be concluded that Electronic Word of Mouth has an influence on Purchase Intention throughBrand Image.Keywords-electronic word of mouth, purchase intention, brand image